Outcome of unstable fractures of the distal end of the radius treated with external fixator - Gupta, HK; Shrestha, R; Shrestha, SK (Journal of College of Medical Sciences-Nepal, 2015)
BACK GROUND AND OBJECTIVES Fracture of the distal radius is the most common fracture treated by the orthopedic surgeons. Although there are several treatment options available today, the aim always remains to restore the anatomy and bring back the function to near normal condition. In this prospective study we intend to evaluate the functional and radiological outcome of the unstable fracture of the distal radius when treated with external fixator. MATERIALS AND METHODS In this hospital based, Prospective study conducted in department of Orthopedics, College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan, during the period from January 2011 to September 2012, 54 patients, (33 male and 21 female) with unstable fracture of the distal end of radius were included in the study. All the patients were treated with external fixator and followed for a period of 12 weeks. RESULT Among 54 patients, 52 were followed up for 12 weeks and two patients were lost to follow up after six weeks. The final result was assessed in detail on the basis of Modification, by Sarmiento et al., of the Demerit Point system of Gartland and Werley at the end of 12 weeks. The result was excellent in 25 cases, good in 19 cases and fair in eight cases. There were no poor results in this series. CONCLUSION External fixator is not only easy to use, allows re-reduction, has lower rate of complications and can be stiff enough to maintain the alignment but it is also a cost effective, patient compliant method which causes lesser morbidity to the patient as compared to the other options available. DOI: http://dx.doi.org/10.3126/jcmsn.v10i2.12950 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 27-32